Induction of liver-specific intrahepatic myeloid cells aggregation expands CD8 T cell and inhibits growth of murine hepatoma. (2nd December 2018) - Lin, Yung-Chang; Hsu, Chen-Yu; Huang, Sheng-Kai; Fan, Yun-Han; Huang, Chien-Hao; Yang, Chan-Keng; Su, Wan-Ting; Chang, Po-Chia; Dutta, Avijit; Liu, Yu-Jen; Huang, Ching-Tai; Chen, Tse-Ching; et al.
ABSTRACT: Toll-Like Receptor 9 (TLR9) stimulation selectively triggers the formation of a cell cluster termed intrahepatic myeloid aggregation for T cell expansion" (iMATE) in a mouse chronic viral hepatitis model. iMATE expands cytotoxic T cells and controls viral hepatitis infection. The liver-specific immune response prompted this investigation of whether the effect could control tumor growth in the murine hepatic tumor model. Murine hepatic BNL cells were used to establish an orthotropic liver tumor model. We found that intravenous infusion of TLR 9 agonist, CpG oligodeoxynucleotide (ODN) induced iMATE formation in non-tumor parts of liver and suppressed the murine BNL tumor growth. The ratio of intra-tumor CD8 + T cells have increased after CpG ODN. These cells expressed higher levels of effector and checkpoint molecules, and produce more Th1 cytokine upon ex vivo stimulation. The CD11b + Ly6C hi Ly6G – subset of CD11b + myeloid cells in the tumor microenvironment has increased. Both CD11b + Ly6C hi Ly6G – and CD11b + Ly6C lo Ly6G + subsets expressed higher level of interferon-gamma post CpG ODN treatment, although still presented a suppressive phenotype. Their suppressive ability was decreased, instead, the targeted CD8 + T cell proliferation was promoted at a higher dose of CD11b + Ly6C hi Ly6G − cells. The phenomenon was further proven in DEN induced liver tumor model. In conclusion, systemic CpG ODN treatment induced iMATE formation that expanded effector CD8 + T cells to control tumor growth in the mouse hepatic tumor model. This novel strategy provides a new rationale for liver-specific tumor immunotherapy.